2020
DOI: 10.1039/d0na00189a
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid hybrid membranes for bacterial & genetic material removal from water and their anti-biofouling properties

Abstract: Water scarcity and contamination by biological pollutants are global challenges that significantly affect public health. Reverse osmosis, nanofiltration and ultrafiltration technologies are very effective for the elimination of pathogens and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
(61 reference statements)
0
7
0
Order By: Relevance
“…However, the removal effect of EPs by an inorganic–organic compound coagulant will be significantly affected by the changes in pH, ionic strength, humic acid concentration, and other factors [ 131 ]. The coagulation mechanism under the coexistence of EPs and other pollutants needs further research and verification [ 17 , 132 , 133 ]. It has been reported that a quaternary amine-group-grafted chitosan flocculant can effectively exert the “breaking-cell-wall” effect, enabling the removal efficiency of E. coli to reach 99% [ 134 ].…”
Section: Contribution Of Pretreatment Scheme For Ep Removalmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the removal effect of EPs by an inorganic–organic compound coagulant will be significantly affected by the changes in pH, ionic strength, humic acid concentration, and other factors [ 131 ]. The coagulation mechanism under the coexistence of EPs and other pollutants needs further research and verification [ 17 , 132 , 133 ]. It has been reported that a quaternary amine-group-grafted chitosan flocculant can effectively exert the “breaking-cell-wall” effect, enabling the removal efficiency of E. coli to reach 99% [ 134 ].…”
Section: Contribution Of Pretreatment Scheme For Ep Removalmentioning
confidence: 99%
“…Ultrafiltration (UF) processes represent a water purification method that is able to achieve relative energy savings, and which is widely used in biological protein separation, medical treatments, and wastewater purification [ 1 , 12 , 13 , 14 ]. Based on the interception effect of UF membranes on organics with different molecular weights, these processes can be adopted to separate macromolecular organics such as proteins, nucleic acids, polysaccharides, humic acids (HAs), and bacteria in wastewater purification [ 12 , 13 , 15 , 16 , 17 , 18 , 19 ]. Yasui et al reported that adopting UF strategies to remove the median of viruses can achieve 2.9 log, much lower than the indicators of human enteroviruses [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Palika et al. have been using slow pressing and drying to produce hybrid membranes with varying proportions of chitosan, ANFs, and carbon [ 23 ]. The hybrid membrane’s active layer was thicker, denser, and significantly more hydrophilic than the ANF's pristine membrane.…”
Section: Preparation and Characteristics Of Amyloid Nanofibrils-based...mentioning
confidence: 99%
“…Moreover, they can adsorb genetic material due to hydrogen bonding, hydrophobic, van der Waals, and electrostatic interactions between the positively charged groups of ANFs and the negatively charged nucleic acids. In addition, it can improve membrane fouling resistance through the coating of polymers [ 23 ]. In order to show the advantages of ANFs-based membrane filtration more clearly, we compared membrane filtration based on ANFs and other methods of bacteria removal in Table S3 .…”
Section: Adsorption Performance Of Amyloid Nanofibrils Based Compositesmentioning
confidence: 99%
See 1 more Smart Citation